Persepsi Masyarakat Terhadap Kemujaraban Pijat Sangkal Putung dalam Mengobati Patah Tulang di Kabupaten Pekalongan - Riska Ayu Setiyani; Fadly Husain (Universitas Hamzanwadi, 2026)
Bone fractures are common injuries, whether caused by accidents, sports injuries, or daily activities. However, in Indonesia, especially Java, traditional treatments such as sangkal putung are a popular choice among the community. Despite modern facilities, many people still believe in the efficacy of Sangkal Putung. This study aims to understand the community's perception of the efficacy of Sangkal Putung massage in treating bone fractures, how Sangkal Putung massage can play a role in traditional and modern health systems, and to determine the community's perception of the risks that may arise from the use of Sangkal Putung massage as a treatment for bone injuries. This study applies the Health Belief Model theory. The research method used is a descriptive qualitative approach, with data triangulation techniques to improve the accuracy and validity of the information. Data were obtained through interviews with various informants, including patients and non-patients, direct observation, and document analysis. The results of this study indicate that public perceptions of Sangkal Putung massage are formed from generations of experience, stories from relatives, and cultural practices, so that this method, which is considered effective or “mandi” in Javanese tradition, is chosen as an alternative treatment for bone injuries, sprains, and minor fractures.